Kajian Hukum Waris Anak Angkat Dalam Perspektif Hukum Islam (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Children In Islamic law, adopted children do not have inheritance rights because there is no blood relationship between them and their adoptive parents. Therefore, it is important to examine this issue from a conceptual perspective within Islamic legal principles. This study aims to determine the legal position of adopted children in the distribution of inheritance according to Islamic law, as well as to identify alternative legal mechanisms that can be applied so that adopted children may receive a portion of the inheritance. The research employs a normative legal method, utilizing a literature review and legislative approach. Based on this perspective, adopted children may receive inheritance from their adoptive parents through a mandatory will (wasiyyah wajibah), which entitles them to up to one-third of the estate. The obligation of a mandatory will applies to anyone who dies and leaves assets but does not make a formal will—part of their estate must be allocated to fulfill this obligation. Thus, the distribution of inheritance to adopted children can be carried out through a wasiyyah wajibah or by way of property donation.